Quantitative imaging of carbon dimer precursor for nanomaterial synthesis in the carbon arc. (6th February 2018) - Vekselman, V; Khrabry, A; Kaganovich, I; Stratton, B; Selinsky, R S; Raitses, Y
Abstract: Delineating the dominant processes responsible for nanomaterial synthesis in a plasma environment requires measurements of the precursor species contributing to the growth of nanostructures. We performed comprehensive measurements of spatial and temporal profiles of carbon dimers (C2 ) in sub-atmospheric-pressure carbon arc by laser-induced fluorescence. Measured spatial profiles of C2 coincide with the growth region of carbon nanotubes (Fang et al 2016 Carbon 107 273–80) and vary depending on the arc operation mode, which is determined by the discharge current and the ablation rate of the graphite anode. The C2 density profile exhibits large spatial and time variations due to motion of the arc core. A comparison of the experimental data with the 2D simulation results of self-consistent arc modeling shows good agreement. The model predicts well the main processes determining spatial profiles of carbon dimers (C2 ).